The development of intensity duration frequency (IDF) curves in Gombak - Aida Zahirah, Zurhaini (2019)
Changing in climate is one of the main parameter that affecting the water resources as it affects the whole hydrologic cycle thus causes variation in rainfall intensity, duration and frequency of precipitation. The study is about development of Intensity Duration Frequency (IDF) curves in Gombak. IDF curve is one of the most commonly used all engineers, developers and contractors to design storm, hydraulic and hydrology structure. The IDF curves in Manual Saliran Mesra Alam (MSMA 2) only updated until year 2012 and covered limited location only. The aim of this study is to developed IDF curves with and without outlier by using Lognormal distribution and Gumbel distribution in Gombak. The Annual Maximum Series (AMS) of rainfall data were collected from Department of Irrigation and Drainage (DID). It consists of eleven rainfall stations. The methods that were used to determine the outlier of IDF curves are U.S. Water Resource Council (1981) and Interquartile Range (IQR). It is clearly shows the greater removal of outliers for Annual Maximum Series (AMS) rainfall data was by using Interquartile Range rather than U.S. Water Resource Council (1981) due to discrepancies between 75th and 25th percentiles that measure the dispersion of statistical study. Lognormal distribution and Gumbel distribution are the methods that were used to develop IDF curves. Based on the analysis, the percentage difference between IDF curves with and without outlier for Lognormal distribution are within 0% to 21.6% while for Gumbel distribution are within 0% to 24.7%. It can be concluded that the percentage of difference between IDF curves with and without outlier using Gumbel distribution is greater than using Lognormal distribution. According to the output, it shows the greater removal of outliers will produce higher percentage of difference (%).